A low-temperature, high-performance polyionic liquid-based solid electrolyte and its preparation method and application

By developing a low-temperature and high-performance polyion liquid reference solid electrolyte, using glycerol-like quasi-solid polymer structure and specific counter ions, the problems of large interface resistance and low ionic conductivity of solid-state batteries in low-temperature environments are solved, and the problem of large interface resistance and low ionic conductivity of solid-state batteries is achieved. High performance and safe solid-state battery.

CN118507819BActive Publication Date: 2025-02-14SHANGQIU NORMAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410570747.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-02-14
Estimated Expiration
2044-05-09

AI Technical Summary

Technical Problem

In a low-temperature environment, solid-state batteries have large interface resistance, which affects battery performance due to the contact problem between active materials and solid-state electrolytes. In addition, the ionic conductivity of existing quasi-solid polyion liquid electrolytes is relatively low at low temperatures, making it difficult to meet the performance of low-temperature batteries. Require.

Method used

Develop a low-temperature high-performance polyion liquid benchmark solid electrolyte, adopting a glycerol-like quasi-solid polymer structure, with imidazolium cations as the polymerization framework, ethyl-terminated polyethylene glycol chains as the substituent, and counter ions are chlorine, Bromine, acrylic acid, FSI, PF6, BF4, TFSI, etc. are prepared by radical initiation polymerization method to obtain electrolytes with high ionic conductivity and good mechanical properties.

Benefits of technology

It realizes high ionic conductivity in low-temperature environments, improves the low-temperature electrochemical performance of solid-state batteries, enhances the rate performance and output power, and improves the safety of the battery through the mechanical properties and non-volatility of polymers, avoids the safety of the battery Safety hazards such as short circuit and explosion inside the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118507819B_ABST
    Figure CN118507819B_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature, high-performance polyionic liquid-based solid electrolyte and a preparation method and application thereof. The low-temperature, high-performance polyionic liquid-based solid electrolyte is a quasi-solid polymer similar to glycerol, has wettability and non-fluidity, uses imidazolium cations as polymer skeletons, ethyl-terminated polyethylene glycol chains as substituents, and counterions as Cl ‑ Br ‑ AA ‑ 、FSI ‑ PF6 ‑ 、BF4 ‑ TFSI ‑ Any one of the above. The low-temperature, high-performance polyionic liquid-based solid electrolyte has semi-solid non-fluidity, excellent wettability and interface compatibility, and a glass transition temperature (Tg) as low as ‑60°C. The higher ionic conductivity, interface compatibility and low-temperature resistance are conducive to improving the low-temperature electrochemical performance of solid-state batteries, and improving the rate performance and output power of solid-state batteries; the good mechanical strength, flexibility and non-volatility of the polymer structure can effectively prevent safety hazards such as internal short circuits and explosions in the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solid electrolyte and energy storage technology, and specifically relates to a low-temperature, high-performance polyionic liquid-based solid electrolyte and a preparation method and application thereof. Background Art

[0002] With the continuous development of lithium / sodium-ion battery technology, solid-state electrolytes have attracted more and more attention due to their advantages such as high safety, long life and fast charging. Compared with liquid electrolytes, solid-state electrolytes have higher mechanical strength and can maintain stable operation of the battery under extreme conditions such as high temperature, low temperature and even puncture. Solid-state electrolytes have stable chemical properties, which makes the battery less prone to side reactions during charging and discharging, thereby improving the cycle life of the battery. In addition, solid-state electrolytes can maintain high ionic conductivity in low or even ultra-low temperature environments, which allows solid-state batteries to operate in a wider temperature range and are particularly suitable for applications in some extreme environments.

[0003] However, the interface resistance between the solid electrolyte and the positive and negative electrodes is large, which affects the performance of the battery, which limits the design and performance of solid-state batteries. Especially in low-temperature environments, the contact problem between the active material and the solid electrolyte becomes more serious. Chinese patents with publication numbers CN 114976234 A and CN 113429504 A report the preparation of quasi-solid-state polyionic liquid electrolytes. These quasi-solid-state electrolyte materials have improved the interfacial contact to a certain extent, but because the conventional polyionic liquid material itself is solid, the prepared composite electrolyte has a high freezing point and low ionic conductivity, which is difficult to meet the low-temperature battery performance. The development of a quasi-solid-state electrolyte material with high ionic conductivity at low temperature, good mechanical properties and excellent compatibility between positive and negative electrodes is of great significance to the development of solid-state battery technology. Summary of the invention

[0004] In order to develop a quasi-solid electrolyte material with low-temperature high ionic conductivity, good mechanical properties and excellent positive and negative electrode compatibility, the present invention provides a low-temperature high-performance polyionic liquid reference solid electrolyte and a preparation method and application thereof.

[0005] The object of the present invention is achieved in the following manner:

[0006] A low-temperature, high-performance polyionic liquid-based solid electrolyte is a glycerol-like quasi-solid polymer with wettability and non-flowability. It uses imidazolium cations as polymer backbones, ethyl-terminated polyethylene glycol chains as substituents, and counterions are any of chloride (Cl) ions, bromide (Br) ions, acrylic acid (AA) roots, bis(fluorosulfonyl)imide (FSI) anions, hexafluorophosphate (PF6) roots, tetrafluoroborate (BF4) roots, and bis(trifluoromethanesulfonyl)imide (TFSI) anions. The specific structural formula is:

[0007]

[0008] The preparation method of the low-temperature high-performance polyionic liquid reference solid electrolyte comprises the following steps: a. When the counter ion is a chloride (Cl) ion or a bromide (Br) ion:

[0009] (1) Preparation of polyethylene glycol-functionalized ionic liquid monomers

[0010] Dissolve 1-vinyl functionalized imidazole and halogenated polyethylene glycol monoethyl ether in equal molar amounts in a solvent, heat and stir at 0-80°C for 6-24 hours to obtain a capped polyethylene glycol functionalized ionic liquid monomer whose counter ion is chloride ion or bromide ion;

[0011] (2) Preparation of polyionic liquid benchmark solid electrolyte PIL-X-(EG)n-Et (n=3~50)

[0012] The prepared end-capped polyethylene glycol functionalized ionic liquid monomer is dissolved in a solvent, an initiator is added, and the mass ratio of the ionic liquid monomer to the initiator is 1:0.01~0.5. The reaction is initiated by a free radical polymerization method, and the reaction is heated and stirred at 55~120°C for 3~24 hours to obtain a low-temperature, high-performance polyionic liquid benchmark solid electrolyte PIL-X-(EG)n-Et (n=3~50);

[0013] b. When the counter ion is acrylic acid (AA) anion, bis(fluorosulfonyl)imide (FSI) anion, hexafluorophosphate (PF6) anion, tetrafluoroborate (BF4) anion, bis(trifluoromethanesulfonyl)imide (TFSI) anion, step (S) is further included between step (1) and step (2):

[0014] (S) Anion Exchange to Prepare Ionic Liquid Monomers with Organic Counterions

[0015] The ionic liquid monomer prepared in step (1) is mixed with an equimolar amount of a salt that can provide any one of the counter ions selected from the group consisting of acrylate, bis(fluorosulfonyl)imide anion, hexafluorophosphate, tetrafluoroborate, and bis(trifluoromethanesulfonyl)imide anion, and an organic solvent is added to fully dissolve and the inorganic salt is filtered out to obtain a capped polyethylene glycol functionalized ionic liquid monomer whose counter ion is any one of the group consisting of acrylate, bis(fluorosulfonyl)imide anion, hexafluorophosphate, tetrafluoroborate, and bis(trifluoromethanesulfonyl)imide anion.

[0016] The polyethylene glycol unit in the halogenated polyethylene glycol monoethyl ether in step (1) is a condensation structure of 3 to 50 ethylene glycol molecules.

[0017] The solvent in step (1) is ethyl acetate, or at least one of acetonitrile, tetrahydrofuran, anhydrous ether, dichloromethane, chloroform, and N,N-dimethylformamide.

[0018] The solvent in step (2) is ethanol, or at least one of ethyl acetate, dichloromethane, chloroform, N,N-dimethylformamide, methanol, and water.

[0019] In step (2), the initiator is any one of azobisisobutyronitrile, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, azobisisoheptanenitrile and benzoyl peroxide.

[0020] The organic solvent in step (S) is ethyl acetate, or at least one of dichloromethane, chloroform, acetonitrile, toluene, ether, and tetrahydrofuran.

[0021] Application of low-temperature, high-performance polyionic liquid-based solid electrolytes as electrolyte materials for lithium / sodium-ion batteries.

[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0023] (1) High ionic conductivity: The polyionic liquid-based solid electrolyte of the present invention has high ionic conductivity and low-temperature resistance, which is beneficial to improving the low-temperature electrochemical performance of solid-state batteries.

[0024] (2) High safety: The polyionic liquid-based solid electrolyte of the present invention has the mechanical properties of polymers, as well as non-flammability and non-volatility, which can effectively prevent safety hazards such as internal short circuits and explosions in batteries.

[0025] (3) Excellent compatibility between positive and negative electrodes: The polyionic liquid-based solid electrolyte of the present invention has good compatibility and interface wettability with positive and negative electrode materials, which can effectively improve the rate performance and output power of solid-state batteries.

[0026] (4) Excellent low-temperature performance: The polyionic liquid-based solid electrolyte of the present invention can still maintain a relatively high ionic conductivity in a low-temperature environment, so that the solid-state battery has good capacity retention and cycle stability under low-temperature conditions.

[0027] The present invention is used as an electrolyte material for sodium ion batteries. -1 At a current density of 1.3 Å, the first reversible capacity at room temperature can reach 430 mA h g -1 ; The first reversible capacity can reach 220 mA hg at -25 °C -1 After 100 cycles, the capacity retention rate is above 45%, showing excellent room temperature and low temperature electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is the structural formula of the polyionic liquid reference solid electrolyte in Example 1.

[0029] Figure 2 This is a graph showing the ionic conductivity data of the polyionic liquid benchmark solid electrolyte in Example 1.

[0030] Figure 3 It is a charge and discharge curve diagram of the polyionic liquid reference solid electrolyte in Example 1.

[0031] Figure 4 It is the structural formula of the polyionic liquid reference solid electrolyte of the present invention. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific examples. It should be understood that the following examples are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0033] A low-temperature, high-performance polyionic liquid-based solid electrolyte is a glycerol-like quasi-solid polymer with wettability and non-flowability. It uses imidazolium cations as polymer backbones, ethyl-terminated polyethylene glycol chains as substituents, and counterions are any of chloride (Cl) ions, bromide (Br) ions, acrylic acid (AA) roots, bis(fluorosulfonyl)imide (FSI) anions, hexafluorophosphate (PF6) roots, tetrafluoroborate (BF4) roots, and bis(trifluoromethanesulfonyl)imide (TFSI) anions. The specific structural formula is:

[0034]

[0035] The preparation method of the low-temperature high-performance polyionic liquid reference solid electrolyte comprises the following steps: a. When the counter ion is a chloride (Cl) ion or a bromide (Br) ion:

[0036] (1) Preparation of polyethylene glycol-functionalized ionic liquid monomers

[0037] Dissolve 1-vinyl functionalized imidazole and halogenated polyethylene glycol monoethyl ether in equal molar amounts in a solvent, heat and stir at 0-80°C for 6-24 hours to obtain a capped polyethylene glycol functionalized ionic liquid monomer whose counter ion is chloride ion or bromide ion;

[0038] (2) Preparation of polyionic liquid benchmark solid electrolyte PIL-X-(EG)n-Et (n=3~50)

[0039] The end-capped polyethylene glycol functionalized ionic liquid monomer prepared in step (1) is dissolved in a solvent, and an initiator is added, wherein the mass ratio of the ionic liquid monomer to the initiator is 1:0.01-0.5, and the reaction is initiated by a free radical polymerization method. The reaction is heated and stirred at 55-120° C. for 3-24 hours to obtain a low-temperature, high-performance polyionic liquid benchmark solid electrolyte PIL-X-(EG)n-Et (n=3-50).

[0040] b. When the counter ion is acrylic acid (AA) anion, bis(fluorosulfonyl)imide (FSI) anion, hexafluorophosphate (PF6) anion, tetrafluoroborate (BF4) anion, bis(trifluoromethanesulfonyl)imide (TFSI) anion, the following steps are included:

[0041] (1) Preparation of polyethylene glycol-functionalized ionic liquid monomers

[0042] Dissolve 1-vinyl functionalized imidazole and halogenated polyethylene glycol monoethyl ether in equal molar amounts in a solvent, heat and stir at 0-80°C for 6-24 hours to obtain a capped polyethylene glycol functionalized ionic liquid monomer whose counter ion is chloride ion or bromide ion;

[0043] (S) Anion Exchange to Prepare Ionic Liquid Monomers with Organic Counterions

[0044] The ionic liquid monomer prepared in the above step (1) is mixed with an equimolar amount of a salt that can provide any one of the counter ions selected from the group consisting of acrylate, bis(fluorosulfonyl)imide anion, hexafluorophosphate, tetrafluoroborate, and bis(trifluoromethanesulfonyl)imide anion, and an organic solvent is added to fully dissolve the inorganic salt and filter out the inorganic salt to obtain a capped polyethylene glycol functionalized ionic liquid monomer whose counter ion is any one of the group consisting of acrylate, bis(fluorosulfonyl)imide anion, hexafluorophosphate, tetrafluoroborate, and bis(trifluoromethanesulfonyl)imide anion;

[0045] (2) Preparation of polyionic liquid benchmark solid electrolyte PIL-X-(EG)n-Et (n=3~50)

[0046] The end-capped polyethylene glycol functionalized ionic liquid monomer prepared in step (S) is dissolved in a solvent, and an initiator is added, wherein the mass ratio of the ionic liquid monomer to the initiator is 1:0.01-0.5, and the reaction is initiated by a free radical polymerization method. The reaction is heated and stirred at 55-120° C. for 3-24 hours to obtain a low-temperature, high-performance polyionic liquid benchmark solid electrolyte PIL-X-(EG)n-Et (n=3-50).

[0047] The solvent in step (1) is ethyl acetate, or at least one of tetrahydrofuran, anhydrous ether, dichloromethane, chloroform, and N,N-dimethylformamide.

[0048] The solvent in step (2) is ethanol, or at least one of ethyl acetate, chloroform, N,N-dimethylformamide, methanol, and water.

[0049] In step (2), the initiator is any one of azobisisobutyronitrile, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, azobisisoheptanenitrile and benzoyl peroxide.

[0050] The organic solvent in step (S) is ethyl acetate, or at least one of dichloromethane, chloroform, acetonitrile, toluene, ether, and tetrahydrofuran. The selection of the organic solvent and its ratio are mainly based on the regulation of the polarity of the solvent, thereby regulating the solubility of the product. The principle is to reduce the polarity of the solvent as much as possible while being able to completely dissolve the product.

[0051] The low-temperature, high-performance polyionic liquid benchmark solid electrolyte PIL-X-(EG)n-Et (n=3~50) prepared above can be used as a lithium / sodium ion battery electrolyte.

[0052] Example 1

[0053] A low-temperature, high-performance polyionic liquid-based solid electrolyte, the preparation method of which comprises the following steps:

[0054] (1) First, 1-vinylimidazole (0.94 g, 10 mmol) and chloropentaethylene glycol monoethyl ether (10 mmol) were dissolved in 10 mL of tetrahydrofuran solution. The solution was heated to 50 °C and refluxed for 12 h, and then the tetrahydrofuran was removed by vacuum distillation. Dichloromethane was added to wash three times, and vacuum dried to obtain a capped polyethylene glycol functionalized ionic liquid monomer with a chloride ion as the counter ion.

[0055] (2) The above-mentioned end-capped polyethylene glycol functionalized ionic liquid monomer whose counter ion is chloride ion and bis(fluorosulfonyl)imide salt (NaFSI) (10 mmol) are uniformly mixed, 30 mL of ethyl acetate is added to fully dissolve, the inorganic salt sodium chloride is filtered out after standing, and vacuum drying is performed to obtain the end-capped polyethylene glycol functionalized ionic liquid monomer whose counter ion is FSI;

[0056] (3) Weigh 1.0 g of the end-capped polyethylene glycol functionalized ionic liquid monomer prepared in step (2), dissolve it in 2 mL of chloroform, add 100 mg of azobisisobutyronitrile, heat in an 80 °C oil bath and stir for 15 h, perform polymerization reaction and vacuum dry to obtain an emulsion quasi-solid polymer electrolyte PIL-FSI-(EG)5-Et.

[0057] The polyionic liquid solid electrolyte material prepared in this embodiment has a chemical structure as shown in Figure 1 As shown, the cation is imidazolium, the counter anion is FSI, and the imidazolium 3-substituent is a pentaethylene glycol monoethyl ether structure.

[0058] The prepared PIL-FSI-(EG)5-Et polymer was vacuum dried at 50 °C for 12 hours, mixed with NaFSI and PVDF in dry acetonitrile at a mass ratio of 0.85:0.1:0.05, and finally vacuum dried for at least 2 days to remove the residual solvent. The ionic conductivity test was performed using an electrochemical workstation. The ionic conductivity test results are shown in Figure 2 As shown, from Figure 2 It can be seen that the ionic conductivity at room temperature is as high as 1.56×10 -3 S cm -1 , at -25 ℃ low temperature, there is still 0.96×10 -3 S cm -1 The high ionic conductivity indicates that the polyionic liquid-based solid electrolyte of the present invention has high ionic conductivity and low temperature resistance.

[0059] The polyionic liquid solid electrolyte material prepared in this example was assembled into a sodium ion battery with commercial hard carbon YHC-2 as the negative electrode. The battery was tested for charge and discharge performance using a LandBT2013A charger and discharger produced by Wuhan Blue Electric. The test results are shown in Figure 3 After testing, at 100 mA g -1 At a current density of 1.3 Å, the first reversible capacity at room temperature can reach 460 mA hg -1 ; The first reversible capacity can reach 290 mA hg at -25 °C -1 After 300 cycles, the capacity retention rate is above 45% (based on the reversible charge capacity), showing excellent room temperature and low temperature electrochemical performance.

[0060] Example 2

[0061] A low-temperature, high-performance polyionic liquid-based solid electrolyte, the preparation method of which comprises the following steps:

[0062] (1) First, 1-vinylimidazole (0.94 g, 10 mmol) and brominated dodecapolyethylene glycol monoethyl ether (10 mmol) were dissolved in 50 mL of ethyl acetate solution. The solution was heated to 20 °C and refluxed for 22 h, and then the ethyl acetate was removed by vacuum distillation. Dichloromethane was added to wash three times, and vacuum dried to obtain a capped polyethylene glycol functionalized ionic liquid monomer with a bromide ion as the counter ion.

[0063] (2) The above ionic liquid monomer and sodium acrylate (NaAA) (10 mmol) were uniformly mixed, and 30 mL of chloroform / ether (v / v, 1 / 2) was added to fully dissolve. After standing, the inorganic salt sodium bromide was filtered out, and vacuum dried to obtain a capped polyethylene glycol functionalized ionic liquid monomer with a counter ion of acrylate;

[0064] (3) Weigh 1.0 g of the end-capped polyethylene glycol functionalized ionic liquid monomer prepared in step (2) with an acrylic acid group as the counter ion, dissolve it in 2 mL of ethyl acetate, add 100 mg of azobisisobutyronitrile, heat in an oil bath at 120 °C and stir for 12 h, polymerize and vacuum dry to obtain an emulsion quasi-solid polymer electrolyte PIL-AA-(EG) 12 -Et.

[0065] The testing and application methods of the polyionic liquid reference solid electrolyte material are the same as those in Example 1.

[0066] The polyionic liquid solid electrolyte material prepared in this example was assembled into a sodium ion battery with commercial hard carbon YHC-2 as the negative electrode. The charge and discharge performance test was carried out according to the test method disclosed in the example. After testing, at 100 mAg -1 At a current density of 1.3 Å, the first reversible capacity at room temperature can reach 420 mA h g -1 ; The first reversible capacity can reach 275mA hg at -25 ℃ -1 After 100 cycles, the capacity retention rate is more than 60% (based on the reversible charge capacity).

[0067] Example 3

[0068] (1) First, 1-vinylimidazole (0.94 g, 10 mmol) and poly(ethylene glycol) bromide monoethyl ether (10 mmol) were dissolved in 100 mL of N,N-dimethylformamide solution. The solution was heated to 80 °C and refluxed for 6 h, and then N,N-dimethylformamide was removed by vacuum distillation. Ether solvent was added for washing three times, and vacuum drying was performed to obtain a capped polyethylene glycol functionalized ionic liquid monomer with a bromide ion as the counter ion.

[0069] (2) The above ionic liquid monomer and sodium hexafluorophosphate (NaPF6) (10 mmol) were uniformly mixed, 100 mL of dichloromethane was added to fully dissolve, the inorganic salt sodium bromide was filtered out after standing, and vacuum dried to obtain a capped polyethylene glycol functionalized ionic liquid monomer with a counter ion of hexafluorophosphate;

[0070] (3) Weigh 1.0 g of the end-capped polyethylene glycol functionalized ionic liquid monomer prepared in step (2), dissolve it in 2 mL of dichloromethane, add 500 mg of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, heat in an oil bath at 120 °C and stir for 3 h, perform polymerization reaction and vacuum dry to obtain an emulsion quasi-solid polymer electrolyte PIL-PF6-(EG) 50 -Et.

[0071] The testing and application methods of the polyionic liquid reference solid electrolyte material are the same as those in Example 1.

[0072] The polyionic liquid reference solid electrolyte material prepared in this example was assembled into a sodium ion battery with commercial hard carbon YHC-2 as the negative electrode. After testing, at a current density of 100 mA g-1, the first reversible capacity at room temperature can reach 450 mAh g-1; at -25 ° C, the first reversible capacity can reach more than 270 mA h g-1, and after 100 cycles, the capacity retention rate is more than 55% (based on the reversible charge capacity).

[0073] Example 4

[0074] (1) First, 1-vinylimidazole (0.94 g, 10 mmol) and triethylene glycol monoethyl ether (10 mmol) were dissolved in 10 mL of acetonitrile solution. The solution was heated under reflux and stirred for 15 h, and then the acetonitrile was removed by vacuum distillation. Ether solvent was added to wash three times, and vacuum dried to obtain a capped polyethylene glycol functionalized ionic liquid monomer with a bromide ion as the counter ion;

[0075] (2) The above ionic liquid monomer and bis(trifluoromethanesulfonyl)imide salt (NaTFSI) (10 mmol) were uniformly mixed, 100 mL of dichloromethane was added to fully dissolve, the inorganic salt sodium bromide was filtered out after standing, and vacuum dried to obtain a capped polyethylene glycol functionalized ionic liquid monomer with a bis(trifluoromethanesulfonyl)imide anion as the counter ion;

[0076] (3) Weigh 1.0 g of the end-capped polyethylene glycol functionalized ionic liquid monomer prepared in step (2), dissolve it in 2 mL of methanol, add 200 mg of benzoyl peroxide, heat in an oil bath at 55 °C and stir for 24 h, perform polymerization reaction and vacuum dry to obtain an emulsion quasi-solid polymer electrolyte PIL-TFSI-(EG)3-Et.

[0077] The testing and application methods of the polyionic liquid reference solid electrolyte material are the same as those in Example 1.

[0078] The polyionic liquid solid electrolyte material prepared in this example was assembled into a sodium ion battery with commercial hard carbon YHC-2 as the negative electrode. After testing, the -1 At a current density of 1.5 Å, the first reversible capacity at room temperature can reach 450 mAh g -1 ; The first reversible capacity can reach 260 mA hg at -25 °C -1 After 100 cycles, the capacity retention rate is above 55% (based on the reversible charge capacity).

[0079] Example 5

[0080] (1) First, 1-vinylimidazole (0.94 g, 10 mmol) and pentaethylene glycol monoethyl ether (10 mmol) were dissolved in 10 mL of tetrahydrofuran solution. The solution was heated to 5°C and refluxed for 24 h, and then the tetrahydrofuran was removed by vacuum distillation. Ethyl acetate was added to wash three times, and vacuum dried to obtain an ionic liquid monomer functionalized with end-capped polyethylene glycol.

[0081] (2) Weigh 1.0 g of the ionic liquid monomer prepared in step (1), dissolve it in 2 mL of anhydrous ethanol, add 50 mg of initiator azobis(isoheptylnitrile), heat in an oil bath at 70 °C and stir for 20 h, perform polymerization and vacuum dry to obtain an emulsion quasi-solid polymer material PIL-Cl-(EG)5-Et.

[0082] The testing and application methods of the polyionic liquid reference solid electrolyte material are the same as those in Example 1.

[0083] The polyionic liquid solid electrolyte material prepared in this example was assembled into a sodium ion battery with commercial hard carbon YHC-2 as the negative electrode. After testing, the -1 At a current density of 1.3 Å, the first reversible capacity at room temperature can reach 420 mAh g -1 ; The first reversible capacity can reach 265 mA hg at -25°C -1 After 100 cycles, the capacity retention rate is above 55% (based on the reversible charge capacity).

[0084] Example 6

[0085] (1) First, 1-vinylimidazole (0.94 g, 10 mmol) and triethylene glycol monoethyl ether (10 mmol) were dissolved in 10 mL of anhydrous ether. The solution was heated to 70 °C and refluxed for 10 h, then the anhydrous ether was removed by vacuum distillation. The solution was washed three times with ether solvent, and vacuum dried to obtain a capped polyethylene glycol functionalized ionic liquid monomer with a bromide ion as the counter ion.

[0086] (2) The above ionic liquid monomer and sodium tetrafluoroborate (NaBF4) (10 mmol) were uniformly mixed, 100 mL of toluene was added to fully dissolve, the inorganic salt sodium bromide was filtered out after standing, and vacuum dried to obtain a capped polyethylene glycol functionalized ionic liquid monomer with a counter ion of bis(trifluoromethanesulfonyl)imide anion;

[0087] (3) Weigh 1.0 g of the end-capped polyethylene glycol functionalized ionic liquid monomer prepared in step (2), dissolve it in 2 mL of ethanol, add 10 mg of benzoyl peroxide, heat in an oil bath at 100 °C and stir for 18 h, perform polymerization reaction and vacuum dry to obtain an emulsion quasi-solid polymer electrolyte PIL-BF4-(EG)3-Et.

[0088] The testing and application methods of the polyionic liquid reference solid electrolyte material are the same as those in Example 1.

[0089] The polyionic liquid solid electrolyte material prepared in this example was assembled into a sodium ion battery with commercial hard carbon YHC-2 as the negative electrode. After testing, the -1 At a current density of 1.5 Å, the first reversible capacity at room temperature can reach 440 mA hg -1 ; The first reversible capacity at -25 ℃ can reach 245A hg -1 As above, after 100 cycles, the capacity retention rate is above 52% (based on the reversible charge capacity).

[0090] The low-temperature, high-performance polyionic liquid-based solid electrolyte provided by the present invention has semi-solid non-fluidity, excellent wettability and interface compatibility, and a glass transition temperature (Tg) as low as -60°C. On the one hand, the higher ionic conductivity, interface compatibility and low-temperature resistance are conducive to improving the low-temperature electrochemical performance of solid-state batteries, and improving the rate performance and output power of solid-state batteries; on the other hand, the good mechanical strength, flexibility and non-volatility of the polymer structure can effectively prevent safety hazards such as internal short circuits and explosions in the battery.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several changes and improvements can be made without departing from the overall concept of the present invention, which should also be regarded as the scope of protection of the present invention.

Claims

1. A low-temperature, high-performance polyionic liquid-based solid electrolyte, characterized in that: It is a quasi-solid polymer similar to glycerol, with wettability and non-flowability. It uses imidazolium cation as the polymer backbone, ethyl-terminated polyethylene glycol chain as the substituent, and the counter ion is any one of chloride (Cl) ion, bromide (Br) ion, acrylic acid (AA) root, bis(fluorosulfonyl)imide (FSI) anion, hexafluorophosphate (PF6) root, tetrafluoroborate (BF4) root, bis(trifluoromethanesulfonyl)imide (TFSI) anion. The specific structural formula is:

2. The method for preparing the low-temperature, high-performance polyionic liquid-based solid electrolyte according to claim 1, characterized in that: a. When the counter ion is a chloride (Cl) ion or a bromide (Br) ion, the steps include: (1) Preparation of polyethylene glycol-functionalized ionic liquid monomers Dissolving 1-vinyl functionalized imidazole and halogenated polyethylene glycol monoethyl ether in equal molar amounts in a solvent, heating and stirring at 0 to 80° C. for a reaction for 6 to 24 hours, and obtaining a capped polyethylene glycol functionalized ionic liquid monomer whose counter ion is chloride ion or bromide ion; (2) Preparation of polyionic liquid standard solid electrolyte PIL-X-(EG)n-Et, n = 3 to 50 The prepared end-capped polyethylene glycol functionalized ionic liquid monomer is dissolved in a solvent, an initiator is added, the mass ratio of the ionic liquid monomer to the initiator is 1:0.01-0.5, a free radical polymerization method is used to initiate the reaction, and the reaction is heated and stirred at 55-120° C. for 3-24 hours to obtain a low-temperature, high-performance polyionic liquid benchmark solid electrolyte PIL-X-(EG)n-Et, where n=3-50; b. When the counter ion is acrylic acid (AA), bis(fluorosulfonyl)imide (FSI) anion, hexafluorophosphate (PF6), tetrafluoroborate (BF4), bis(trifluoromethanesulfonyl)imide (TFSI) anion, step (S) is further included between step (1) and step (2). (S) Anion Exchange to Prepare Ionic Liquid Monomers with Organic Counterions The ionic liquid monomer prepared in step (1) is mixed with an equimolar amount of a salt that can provide any one of the counter ions selected from the group consisting of acrylate, bis(fluorosulfonyl)imide anion, hexafluorophosphate, tetrafluoroborate, and bis(trifluoromethanesulfonyl)imide anion, and an organic solvent is added to fully dissolve and filter out the inorganic salt to obtain a capped polyethylene glycol functionalized ionic liquid monomer whose counter ion is any one of the group consisting of acrylate, bis(fluorosulfonyl)imide anion, hexafluorophosphate, tetrafluoroborate, and bis(trifluoromethanesulfonyl)imide anion.

3. The method for preparing the low-temperature, high-performance polyionic liquid-based solid electrolyte according to claim 2, characterized in that: The polyethylene glycol unit in the halogenated polyethylene glycol monoethyl ether in step (1) is a condensation structure of 3 to 50 ethylene glycol molecules.

4. The method for preparing the low-temperature, high-performance polyionic liquid-based solid electrolyte according to claim 2, characterized in that: The solvent in step (1) is ethyl acetate, or at least one of acetonitrile, tetrahydrofuran, anhydrous ether, dichloromethane, chloroform, and N,N-dimethylformamide.

5. The method for preparing the low-temperature, high-performance polyionic liquid-based solid electrolyte according to claim 2, characterized in that: The solvent in step (2) is ethanol, or at least one of ethyl acetate, dichloromethane, chloroform, N,N-dimethylformamide, methanol, and water.

6. The method for preparing the low-temperature, high-performance polyionic liquid-based solid electrolyte according to claim 2, characterized in that: In step (2), the initiator is any one of azobisisobutyronitrile, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, azobisisoheptanenitrile and benzoyl peroxide.

7. The method for preparing the low-temperature, high-performance polyionic liquid-based solid electrolyte according to claim 2, characterized in that: The organic solvent in step (S) is ethyl acetate, or at least one of dichloromethane, chloroform, acetonitrile, toluene, ether, and tetrahydrofuran.

8. The use of the low-temperature, high-performance polyionic liquid reference solid electrolyte as claimed in claim 1, characterized in that: The low-temperature, high-performance polyionic liquid-based solid electrolyte is used as an electrolyte material for lithium / sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method of semi-solid polyion liquid electrolyte for lithium battery

    CN113429504A

  • Polyion liquid electrolyte for lithium-sulfur battery as well as preparation method and application of polyion liquid electrolyte

    CN114976234A

  • Annular nano germanium dioxide / polyion liquid composite material and preparation method and application thereof

    CN110729464A

  • Self-supporting brush-shaped polyion liquid-based electrolyte membrane and preparation method and application thereof

    CN116544495A